Comparison of Visual Analog Pain Score Reported to Physician vs Nurse in Postoperative Foot and Ankle Patients. Issue 4 (16th October 2019) - McBride, Trevor; Martin, Kevin; Wilke, Aaron Joseph; Chisholm, Jamie
Category: Patient Reported Outcome Measures Introduction/Purpose: The relativity of pain adds to the increasing ambiguity of deciding proper treatment procedures. Reliable and validated patient reported outcome measures have attempted to solve this problem, but there are still flaws due to the subjective nature of pain. This study is the third part to two previous studies that found both operative and new nonoperative patients overemphasize their pain scores when reporting to the treating physician as compared to a nurse. This current study aims to examine if this phenomenon holds true with orthopedic postoperative patients. The importance of this study is to observe this phenomenon, as to better understand subjective pain scores. We hypothesize there will be no differences in postoperative patients' pain scores when reporting to a treating physician versus a nurse. Methods: This study is a retrospective cohort of consecutive postoperative foot and ankle patients treated by a single surgeon. The patients were asked to rate their pain intensity by the nursing staff and then by the surgeon using a standard horizontal visual analog scale (VAS) 0 to 10, from "no pain" to "worst pain" at 2, 6, and 12 weeks postoperatively. Differences in reported pain levels were analyzed within each clinic visit. Results: Two hundred and one patients each with 3 follow up encounters were included in our cohort. The mean 2, 6, and 12- week postoperative VAS scores reported to the physician were 2.85, 2.04, and 2.33 respectively; in comparison, the scores reported to the nurse were 2.52 (p=0.0005), 1.77 (p=0.002), and 2.02 (p=0.005) respectively. There was no significant relationship between time and type of provider. Conclusion: This study found that postoperative patients report their pain more consistently to physicians and nursing staff with no clinically significant differences noted. These findings stand in stark contrast to our two previous studies which noted new and preoperative patients reported significantly higher VAS scores to the physician. The reason for reporting inconstancies is unclear, but postoperatively patients no longer need to emphasize their impairments or injury. Postoperatively, they also have a defined time interval and more acute recollection of their pain potentially leading to more consistency in reporting.